Biocitizenship : the politics of bodies, governance, and power - Happe, Kelly E.; Johnson, Jenell M., 1978-; Levina, Marina, 1975- (Biopolitics (New York, N.Y.), 2018)
"Biocitizenship: The Politics of Bodies, Governance, and Power is a critical study of the relationship between the concept of citizenship and the body"--